The use of design in Finnish manufacturing firms - Maarit Lindström; Mika Pajarinen (The Research Institute of the Finnish Economy (ETLA), 2006)
This study analyzes the use of design and the position of the design function in Finnish manufacturing firms. We also study the impact of design on companies' business performance. The paper is based on a survey directed to the member companies of the Confederation of Finnish Industries (EK) in November-December 2005. According to the results, design use in manufacturing companies is still on a relatively low level. Design use varies clearly among analyzed companies, though. Results show that the nature of design use and the position of the design function explain the influence of design on business notably. The impact of design on business through most studied effect channels, such as increase in sales, is statistically significantly higher in those companies in which design is an integrated part of the company's core functions and strategy, and in which design is used continuously. Results also indicate that the use of design in manufacturing firms in Finland will increase in the forthcoming years (2005-2010). – – Tutkimuksessa tarkastellaan suomalaisten teollisuusyritysten muotoilun käyttöä ja asemaa. Lisäksi selvitetään muotoilun vaikuttavuutta yritysten liiketoimintaan. Tutkimus perustuu Elinkeinoelämän keskusliiton EK:n jäsenyrityksille marras-joulukuussa 2005 suunnattuun kyselyyn. Tutkimustulosten mukaan muotoilun käyttö teollisuudessa on edelleen verrattain vähäistä. Muotoilun käyttö kuitenkin poikkeaa selvästi tarkasteltujen yritysten keskuudessa. Tulosten mukaan muotoilun käytön luonne ja asema määrittävät muotoilun vaikuttavuutta selvästi. Sellaiset yritykset, joissa muotoilu on integroitu osa yrityksen muita toimintoja ja strategiaa ja joissa muotoilun käyttö on luonteeltaan jatkuvaa, muotoilun positiivinen vaikutus on havaittavissa useimpien tutkittujen vaikutuskanavien, kuten tuotteiden ja palvelujen myynnin kasvun kohdalla. Seuraavien viiden vuoden aikana (2005-2010) teollisuusyritysten muotoilun käyttö on kasvussa.
Keywords: L20; L25; L60; M21; 330; Design; firm performance; manufacturing; economic performance; design management; Muotoilu; kilpailukyky; teollisuus; liiketoiminta; muotoilujohtaminen